2005
DOI: 10.1126/science.1115901
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Probing the Function of Noncoding RNAs Finds a Repressor of NFAT

Abstract: Noncoding RNA molecules (ncRNAs) have been implicated in numerous biological processes including transcriptional regulation and the modulation of protein function. Yet, in spite of the apparent abundance of ncRNA, little is known about the biological role of the projected thousands of ncRNA genes present in the human genome. To facilitate functional analysis of these RNAs, we have created an arrayed library of short hairpin RNAs (shRNAs) directed against 512 evolutionarily conserved putative ncRNAs and, via ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
534
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(543 citation statements)
references
References 22 publications
6
534
1
2
Order By: Relevance
“…Another example is a paternally imprinted gene H19 (O'neill, 2005), with a conserved secondary structure but non-conserved ORFs, that functions as a tumor suppressor in some tumor types and may play a significant role in tumorigenesis in other types (Steenman et al, 1994;Lottin et al, 2002;Manoharan et al, 2003). Recently, Willingham et al (2005) identified an ncRNA designated NRON that is a repressor of nuclear factor of activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is a paternally imprinted gene H19 (O'neill, 2005), with a conserved secondary structure but non-conserved ORFs, that functions as a tumor suppressor in some tumor types and may play a significant role in tumorigenesis in other types (Steenman et al, 1994;Lottin et al, 2002;Manoharan et al, 2003). Recently, Willingham et al (2005) identified an ncRNA designated NRON that is a repressor of nuclear factor of activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…NRON RNA interacts with proteins including members of the ␤-importin superfamily and a calmodulin-binding protein (IQGAP1), all of which show a repressive effect on NFAT activity. Further studies have revealed that NRON RNA is in a complex with members of the ␤-importin family and negatively regulates the nuclear trafficking of NFAT, rather than directly modulating its transcriptional activity (Willingham et al 2005). The mode of action of NRON ncRNA has highlighted an example of how a ncRNA (NRON) inhibits the activity of a transcription factor (NFAT) primarily by preventing its nuclear import.…”
Section: Nron (Noncoding Repressor Of Nfat [Nuclear Factor Of Activatmentioning
confidence: 99%
“…Shultz and colleagues (Willingham et al 2005) recently undertook an RNAi-based genetic screen in mammalian cell lines and identified the involvement of several ncRNAs in various cellular pathways. One of the ncRNAs identified in the screen, NRON RNA (0.8-3.7 kb), acts as a repressor of NFAT.…”
Section: Nron (Noncoding Repressor Of Nfat [Nuclear Factor Of Activatmentioning
confidence: 99%
“…LncRNAs regulate gene expression at the epigenetic, transcriptional and post-transcriptional levels in diverse biological contexts[6]. In addition, a variety of molecular mechanisms were used as major regulators of these function, such as modulating histone modifications[11], interfering the transcription [12,13], regulating patterns of alternative splicing [14,15],generating small RNAs[16], and modulating protein activation and localization[17]. …”
Section: Introductionmentioning
confidence: 99%